Prevalence of ulcer disease among patients with diabetes mellitus at Royal Prima Hospital Medan - Tua, Grace Angelina Tarigan; Amir, Widya Pasca; Suandy, Suandy; Sopacua, Erwin; Handayani, Putri; Tambunan, Adrian Nurrachman; Putra, Ananda Rahmat; Rahimi, Armon (Buletin Kedokteran & Kesehatan Prima, 2026)
Background: Diabetes mellitus is a chronic metabolic disorder with a rapidly increasing prevalence, often leading to serious complications such as diabetic ulcers, which significantly affect quality of life and increase healthcare costs. This study aimed to determine the prevalence of ulcers in patients with diabetes mellitus treated at Royal Prima Medan Hospital and to analyze the associated factors. Methods: This quantitative observational study employed a retrospective design and analyzed medical record data collected between 2021 and 2025. A total of 58 patients were selected using purposive sampling. Data analysis was conducted using the Chi-Square test and ANOVA with a 95% confidence level. Results: The majority of the respondents were male (63.8%) and within the 56–65-year age group (34.5%). The most common skin condition was diabetic ulcers (82.8%), followed by diabetic bullae (12.1%) and viral infections (5.2%). The mean blood glucose level was 246.33 mg/dL, indicating hyperglycemia. Statistical analysis revealed no significant association between gender and skin disease type (p = 0.895) and no significant difference in blood glucose levels across types of skin disease (p = 0.135). Conclusion: There was no significant correlation between skin disease type and blood glucose levels, suggesting that clinical management should also address other behavioral and metabolic factors.